Phân tích lý thuyết trò chơi ba chiều trong quá trình doanh nghiệp xử lý ô nhiễm môi trường - Lâm Bình, Ên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study aims to analyze the determinants and balance the benefits of relationships between government, enterprise, and non-government organization in the treatment of environmental pollution. By using the method of building a game theory pattern, a three-player game model has been employed to analyze the interesting relationships between government, enterprise, and non-government organization. The results suggest that the use of high fines from the government on the enterprises which cause pollution will be more effective than high subsidies. Besides, if the government increases fines and subsidies policy, the enterprises will lessen the positive handling of pollution and regulation under the environmental regulations. The level of environmental supervision from non-government organization will affects the inspection of the government but not directly affected to the enterprise. Therefore, in order to achieve sustainable economic development, it is necessary to develop a mechanism for rewarding, maintaining and supporting the development of non-governmental organizations and encouraging enterprises to create and apply new technologies.